The Institution of Dismissal of a Claim as Clearly Unfounded as an Created by the Legislator a Potential Mechanism to Interrupt the Limitation Period Without Incurring Any Costs? - Tomczak, Tomasz (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
In 2019 into the Polish civil procedure the institution of dismissal of a claim as clearly unfounded was introduced. Within the framework of this article, the author intends to present and consider one seemingly unplanned effect, to which the introduction of Art. 1911 k.p.c. may lead, i.e. consequence in the form of creating, under certain circumstances, a mechanism enabling the entitled person to interrupt the limitation period without incurring any costs. As this was not the purpose of introducing the considered institution, the rest of the article considers, on the basis of procedural law, how such an unwanted effect should be avoided.